Drying kinetics, modelling and total flavonoid content of Phyllanthus niruri L. under different drying temperature. Issue 1 (1st December 2022) - Agusta, W; Maisaroh,; Hermansyah, H D; Anggraeni, D; Astuti,; Harianto,; Purwanto, W; Manalu, L P
Abstract: Phyllanthus niruri L. drying kinetics were empirically examined at the temperature of 40 °C, 45 °C, 50 °C, 55 °C, and 60 °C in an air-drying oven. The herbs' aerial components (stems, leaves, and flowers) were picked after 9-10 weeks of planting. The drying procedure ended when the sample weights remained unchanged. The drying time varied from 7 to 20.5 hours. CurveExpert Professional was utilized to establish the optimal modeling fit. According to the statistical analysis, notably for the root mean square error ( RMSE ), determination coefficient ( R 2 ), and residual chi-square ( χ 2 ), Midilli-Kucuk has deemed the optimal function for characterizing the kinetics of P. niruri drying. The effective diffusivity and drying activation energy of P. niruri were reported to be 4.050x10 -9 m 2 /s – 1.620x10 -8 m 2 /s and 55.23 kJ/mol, respectively. UV-VIS spectrophotometry was also employed to analyze the effects of the temperature on flavonoid content. The measurement showed that the flavonoid content from all dried herbs varied from 1.18-1.69 %, which already meets the Farmakope Herbal Indonesia's standard. The highest flavonoid content was found at the lowest drying temperature.